Comparison of Catheterization Rates Following Catheter Removal on the First Versus Fifth Postoperative Day After Transurethral Resection of the Prostate - Ranjha, Waqas Ahmed; Zafar, Muhammad Rafiq; Khan, Sajjad; Khoso, Mujahid Ali; Fawad, Muhammad; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the re-catheterization rate after catheter removal on 1st versus 5th postoperative day after transurethral resection of prostate (TURP) for management of benign prostate enlargement. Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi, Pakistan, from Jun 22 May 23.Methodology: After ethical approval of study, two groups were constituted of a sample collected through non-probability consecutive sampling. Consultant urologists and senior registrars performed all transurethral resections of prostate surgeries under spinal anesthesia. After surgeries, irrigation was done with Normal Saline. The catheter was removed on 1st Post op day in one group, while on 5th post-operative day in another group, and the data were recorded in SPSS.Results: The primary outcome was frequency of re-catheterization. The re-catheterization was required in 3(5%) patients after early catheter removal, that is, on day one after TURP, who were kept in Group-1, while 5(8.3%) patients who required re-catheterization were in Group-2 with a p-value of 0.008.Conclusion: It was concluded that early catheter removal had a better outcome and a lesser need for re-catheterization as compared to late catheter removal after transurethral resection of prostate (TURP) done for management of benign prostatic hypertrophy.